Classroom Language Proficiency of EFL Teachers at the Dakhil Level in Aliya Madrasas of Bangladesh: An Empirical Study - Ashraf, Tasleem Ara (International Journal of Language Education, 2025)
In Bangladesh, EFL learning in Aliya madrasas is still questionable as the English language proficiency of the students are far below the acceptable level. According to BANBEIS and World Bank (2018), there are huge dropouts that occur at Dakhil (equivalent to secondary) level in majority Aliya madrasas due to receiving failing grades in English language courses regularly. The poor English language proficiency of Madrasa students is also a result of ineffective teaching and insignificant use of target language by EFL teachers at Dakhil level. Therefore, EFL teachers at Dakhil level in the Aliya madrasas in Bangladesh need to have a very good oral proficiency of English language along with their content knowledge for effective teaching and learning. The purpose of this study was to examine the CLP (classroom language proficiency) of the teachers at Dakhil level who are currently teaching English language in different Aliya madrasas in Bangladesh. This research also investigated EFL learning and teaching in Aliya madrasas using classroom observation and explored the prevailing teaching methods of the teachers. Following qualitative methods of classroom observation and interviews, data were collected from thirty currently practicing teachers who are working at the secondary level in the Aliya madrasas in Bangladesh. Major findings revealed EFL teachers poor proficiency in the usage of target language, as the classroom observations reported I) Insignificant use of TL inside classrooms II) inadequacy in learner interaction using TL, III) limited scope for learner participation IV) lecture based classrooms V) vast  use of native language VI) TTT beyond limits etc. Therefore, this research came up with some recommendations that may help to bring qualitative changes among the teaching learning situation in the Aliya madrasas in Bangladesh.